Penerapan Model Ekspositori Berbantuan Media Miniatur Terhadap Hasil Belajar IPA Peserta Didik di Kelas VI SDN No. 3 Tinambung Kabupaten Majene - Ahmad Munadi Alfarizi Taqwa; Hilmi Hambali; Nurfadilah Nurfadilah (Concept: Journal of Social Humanities and Education, 2024)
This type of research is Pre-Experimental research with a pre-test and post-test group design which aims to determine student learning outcomes after implementing the expository model assisted by miniature media on student learning outcomes in class VI of SDN No. 3 Tinambung Majene Regency. The sample for this research was 29 class VI students. This research was carried out in 6 meetings, and the material presented during the research was the solar system. The data analysis technique used in this research uses descriptive statistical analysis.The research results showed that the average pretest score was 52.24 and the average posttest score was 86.55. Apart from that, N-Gain analysis shows that the average normalized gain of 0.70 is in the high category. From these results it can be concluded that the application of the expository model assisted by miniature media on the science learning outcomes of students in class VI of SDN No. 3 Tinambung Majene Regency.